PENGARUH STRUKTUR MODAL, LIKUIDITAS, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021) - Nopita Sari; Budi Astuti; Yusmaniarti Yusmaniarti; Marini Marini (Universitas Muhammadiyah Bengkulu, 2024)
This research aims to examine the influence of capital structure, liquidity, profitability and company size on company value in manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2021 period. The results of this research show the significance of each variable. Capital Structure has no significant effect on company value with a significant 0.656, Liquidity has a significant effect on company value with a significant 0.869, Profitability has a significant effect on company value with a significant 0.001, Company Size has a significant effect on company value with a significant 0.775. The results of the coefficient of determination test (Adjusted R²) show that 11.6% of the variation in agency costs can be explained by independent variables, while the remaining 88.4% is explained by other variables not in this study. Keywords : Firm Value, Capital Structure, Liquidity, Profitability, and company size.